(untitled) (Iraqi Journal of Medical Sciences, 2019)
Medicinal fungi are those fungi, which produce medically significant metabolites or can be induced to produce such metabolites using biotechnology. The range of medically active compounds that have been identified include antibiotics, anti-cancer drugs, cholesterol inhibitors, psychotropic drugs, immunosuppressants and even fungicides. Although initial discoveries centered on simple molds of the type that cause spoilage of food, later work identified useful compounds across a wide range of fungi. Keywords:Medicinal, fungi Citation:Al-Attraqchi AAF. Medicinal fungi. Iraqi JMS. 2019; 17(1): 1-3. doi: 10.22578/IJMS.17.1.1